The Influence of Transcultural Nursing Based on Health Education on Knowledge, Attitude, Mother Actions and Family Support among Breastfeeding Mother - Yulia Meiliany Naragale; Tiyas Kusumaningrum; Retnayu Pradanie (Pediomaternal Nursing Journal, 2020)
Introduction: Providing additional food other than breast milk before 2-year-old babies in Kupang City are babies given "regal" biscuits, "milcuit" biscuits, and "banana" s because the baby does not feel hungry. Providing "regal" biscuits, "milna" and "banana" biscuits as a complement to give breastfeeding before the age of 2 years because parents believe these biscuits can eliminate hunger for the baby. The purpose of this study was to explain the effect of Transcultural Nursing-based health education on knowledge, attitudes, actions of mothers, and family support in breastfeeding.Methods: The design of this study was a Pre-Experimental study using quantitative data. Samples of 30 breastfeeding mothers who visited the Bakunase Public Health Center in Kupang City of East Nusa Tenggara and were obtained using the total sampling technique. Data obtained from the knowledge questionnaire, attitude questionnaire, action questionnaire, and social and family support questionnaire were then analyzed using the Wilcoxon statistical test.Results: The results showed that there was an influence of transcultural nursing-based health education on knowledge, attitudes, mother actions, social and family support in breastfeeding with a significant value of p=0.000.Conclusion: Transcultural nursing-based health education influences maternal knowledge, maternal attitudes, and family support for mothers in breastfeeding. Subsequent researchers can then carry out transcultural nursing-based health education research on different targets. They can analyze factors related to knowledge, attitudes, actions, and family support for nursing mothers.